2013
DOI: 10.1088/0964-1726/22/2/025032
|View full text |Cite
|
Sign up to set email alerts
|

Giant magnetoresistance effects in gel-like matrices

Abstract: We present transport measurements with magnetoresistance effect amplitudes of up to 260% at room temperature obtained in granular systems consisting of Co nanoparticles embedded in conductive gels as a non-magnetic matrix. In order to gain a better understanding of the transport mechanism in gel during measurement, the granular system was simultaneously monitored by optical microscopy. Gel-like matrices with different conductivities and viscosities were tested and will allow us to realize a highly sensitive gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 11 publications
1
36
0
Order By: Relevance
“…At the same time, there are strong advances in the field of GMR sensorics based on magnetic particles and operating at room temperature. 21 , 26 , 45 , 46 A GMR of up to 260% was reported at room temperature for granular systems consisting of carbon-coated Co nanoparticles of 18-nm diameter embedded in conductive gel-like nonmagnetic matrices. 46 The large magnitude of the GMR effect is promising to realize printable magnetic field sensors.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, there are strong advances in the field of GMR sensorics based on magnetic particles and operating at room temperature. 21 , 26 , 45 , 46 A GMR of up to 260% was reported at room temperature for granular systems consisting of carbon-coated Co nanoparticles of 18-nm diameter embedded in conductive gel-like nonmagnetic matrices. 46 The large magnitude of the GMR effect is promising to realize printable magnetic field sensors.…”
mentioning
confidence: 99%
“… 21 , 26 , 45 , 46 A GMR of up to 260% was reported at room temperature for granular systems consisting of carbon-coated Co nanoparticles of 18-nm diameter embedded in conductive gel-like nonmagnetic matrices. 46 The large magnitude of the GMR effect is promising to realize printable magnetic field sensors. However, the choice of gels for the conductive matrix imposes limitations on thermal stability of the sensing elements in the relevant temperature range from 0 °C up to +85 °C, as required for applications in consumer electronics.…”
mentioning
confidence: 99%
“…salt-containing biogels. For Co nanoparticles, magneto-transport measurements at room temperature revealed GMR effects of more than 200% (see Figure 7 ), which is far above the values known from common systems [ 62 , 63 , 64 ]. Regarding technological relevance, this results in enhanced sensor sensitivity.…”
Section: Nanogranular Gmrmentioning
confidence: 75%
“…148 Recently, Meyer et al reported a GMR of up to 260% at room temperature for granular systems consisting of carboncoated Co nanoparticles of 18 nm in diameter, embedded in conductive gel-like non-magnetic matrices (Figure 10(a)). 149 The magnitude of the GMR effect and the switching behavior of the particle-gel mixture was found to be dependent on the density of magnetic nanoparticles in the direction of the external field (Figure 10(b)). The large magnitude of the GMR effect is promising to realize printable magnetic field sensors.…”
Section: B Nanoparticle-based Giant Magnetoresistive (Gmr) Sensorsmentioning
confidence: 97%